2012
DOI: 10.1021/mz3003787
|View full text |Cite
|
Sign up to set email alerts
|

Substituted Tris(2-pyridylmethyl)amine Ligands for Highly Active ATRP Catalysts

Abstract: General:Materials. All chemicals were purchased from commercial sources, e.g., Aldrich, TCI, and used as received if not stated otherwise. Tris(2-pyridylmethyl) amine (TPMA) was purchased from ATRP Solutions. Methyl acrylate (MA) and butyl acrylate (BA) were passed through a column filled with basic alumina to remove inhibitor prior to use. All manipulations for atom transfer radical polymerizations were performed with oxygen free solvents, degassed by at least three Freeze-Pump-Thaw cycles (FPT), using standa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
93
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 97 publications
(101 citation statements)
references
References 49 publications
7
93
0
Order By: Relevance
“…The large difference in K ATRP values can be attributed mostly to an increase in the activation rate constant (k a , 8400 M -1 s -1 v.s. 3.8 M -1 s -1 ), indicating that Cu I (TPMA *3 )Br should be much more active in ATRP, as confirmed by recently published study (91). …”
Section: Electrochemical Studies and Stability Constants For Copper Csupporting
confidence: 79%
See 3 more Smart Citations
“…The large difference in K ATRP values can be attributed mostly to an increase in the activation rate constant (k a , 8400 M -1 s -1 v.s. 3.8 M -1 s -1 ), indicating that Cu I (TPMA *3 )Br should be much more active in ATRP, as confirmed by recently published study (91). …”
Section: Electrochemical Studies and Stability Constants For Copper Csupporting
confidence: 79%
“…This approach indeed seems to be justified, as demonstrated in a recent study which showed that EDGs in the para-substituted 2,2′-bipyridine ligands can significantly enhance catalytic activity in ATRP (88). In a related work, inspired by the synthetic modifications of TPMA ligand for copper catalyzed oxygen activation (89) and iron mimicking site for methane monooxygenase (90), even more active Cu II X 2 /TPMA *3 (X=Br or Cl, TPMA *3 = tris((4-methoxy-3,5-dimethylpyridin-2-yl)methyl)amine) in situ system was discovered containing a total of nine EDGs (91). This catalyst attained excellent polymerization results in photoATRP (92)(93)(94) of acrylates and emerged as one of the most active ATRP systems nowadays.…”
Section: Development Of Highly Active Copper Complexes For Atra and Atrpmentioning
confidence: 99%
See 2 more Smart Citations
“…[56][57][58][62][63][64] Such information is crucial for a comparison of these techniques to evaluate their potential industrial application, since the ultimate goal of a CRP technique is to produce a wide range of average chain lengths at acceptable polymerization rates while preserving control over PDI and EGF. In this work, such detailed kinetic modeling study is presented for the bulk ICAR ATRP of nBuA using the commercially available N,N,N 0 ,N 00 ,N 00 -pentamethyldiethylenetriamine (PMDETA)…”
Section: Introductionmentioning
confidence: 99%